2018
DOI: 10.7573/dic.212528
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in renal cell carcinoma: latest evidence and clinical implications

Abstract: Advances in understanding the mechanisms of tumour-induced immunosuppression have led to the development of immune-checkpoint inhibitors in cancer patients, including those with renal cell carcinoma (RCC). The optimal combination between immunotherapy and targeted agents (as well as the possible favourable sequential therapy of these two classes of drugs) remains an open question at this moment. Several trials are currently underway to assess the combination of anti-programmed-death 1 (PD-1) or anti-PD-ligand(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…Since then, and with the advent of immune-checkpoint inhibitors, several clinical trials have shown and are still addressing the effect of combining agents targeting PD-L1/PD-1 with anti-VEGFR tyrosine kinase inhibitors (TKI) [85]. The success indicated by these studies led to the recent approval of Nivolumab, which proved better in improving overall-survival and also was better tolerated when compared to everolimus in VEGF-refractory patients [86].…”
Section: Immune Therapies -Brief Overview In Kidney Cancermentioning
confidence: 99%
“…Since then, and with the advent of immune-checkpoint inhibitors, several clinical trials have shown and are still addressing the effect of combining agents targeting PD-L1/PD-1 with anti-VEGFR tyrosine kinase inhibitors (TKI) [85]. The success indicated by these studies led to the recent approval of Nivolumab, which proved better in improving overall-survival and also was better tolerated when compared to everolimus in VEGF-refractory patients [86].…”
Section: Immune Therapies -Brief Overview In Kidney Cancermentioning
confidence: 99%
“…ChRCC came to a similar conclusion [23]. Immunotherapy has also recently emerged as another option to treat metastatic RCC, and clinical trials that compare TKI therapy vs. immunotherapy are currently underway, although these studies have only enrolled patients with ccRCC [24]. e role of immunotherapy in treating nccRCC, for now, remains an open question.…”
Section: Case Reports In Urologymentioning
confidence: 93%
“…Similarly, expression of PD-1 by the TILs or expression of PD-L1 by the tumour cells are both associated with worse prognosis in ccRCC [22,23]. In turn, immunotherapy in forms of PD-1/PD-L1 inhibition appears to be useful in ccRCC management, and monoclonal antibodies targeting PD-1/PD-L1 may be combined with tyrosine kinase inhibitors (TKIs) and CTLA4 inhibitors [24,25].…”
Section: Introductionmentioning
confidence: 99%